Mxene-polymer composite, semiconducting layer for power cable comprising same and power cable
Patent Information
- Application Number
- KR1020210154284
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-11-10
Abstract
Description
Technology Field
[0001] The present invention relates to a MXene-polymer composite, a semiconducting layer for a power cable comprising the same, and a power cable. Background Technology
[0002] Power cables can be composed of a conductor, an inner semiconducting layer, an insulating layer, an outer semiconducting layer, and a sheath layer. In particular, the inner semiconducting layer plays a crucial role in enhancing the electrical characteristics of the cable during manufacturing by improving the interfacial roughness between the conductor and the insulating layer and forming an insulation resistance gradient.
[0003] In order to design such semiconducting insulators, semiconducting compounds containing approximately 40 wt% or more of carbon black (CB) have conventionally been used, and their volume resistivity is approximately 10 to 103 Ω·m. However, this excessive amount of carbon black increases the melt viscosity during extrusion, which reduces processability and causes problems with production efficiency. Furthermore, the excessive carbon black forms protrusions on the surface of the processed semiconducting layer, causing localized insulation breakdown due to the electric field concentrated from the protrusions. This insulation breakdown occurs repeatedly over a long period of time, eventually leading to the loss of function of the power cable.
[0004] To solve the above problems, low-dimensional carbon nanomaterials such as graphene and carbon nanotubes, which have excellent conductivity and low density, have been used. For example, in 'Semiconducting compound for high-voltage or ultra-high-voltage power cables and ultra-high-voltage power cable applying the same (Registration No.: 10-1480009)', a semiconducting layer composition capable of reducing volume resistivity and suppressing surface protrusions was developed by using carbon nanotubes, carbon nanoflakes, or a mixture of these in appropriate proportions. In addition, in 'Lightweight power cable manufactured using a semiconducting composition and an insulating composition (Registration No.: 10-1408925)', a semiconducting layer composition with reduced volume resistivity was developed by simultaneously using carbon nanotubes and carbon black or graphene with respect to a polyolefin resin.
[0005] Meanwhile, in 2011, a new class of two-dimensional crystalline transition metal carbides called MXenes was developed at Drexel University. The synthesis of MXenes with various compositions has been reported, and these MXenes possess excellent metallic conductivity comparable to that of graphene; they have been used in applications requiring high electrical conductivity, such as electromagnetic shielding and electrode materials for flexible devices. Furthermore, MXenes offer advantages in maintaining their crystallinity due to their large surface area relative to their thickness, as well as their relatively easy exfoliation through manufacturing processes, including physical etching. When synthesized in solution, MXenes form numerous functional groups on their surface during the manufacturing process; these groups, particularly the numerous hydroxyl groups (-OH), facilitate water dispersion and enable chemical reactions with other molecules and materials.
[0006] Accordingly, the present invention was completed by confirming the possibility that when MXene, which has excellent electrical conductivity and a large surface area, is applied as a semiconducting layer material, it not only contributes to reducing the filler content but also effectively enhances the electrical conductivity of the semiconducting layer, and effectively disperses it within the matrix resin by introducing a polymer having functional groups that can interact with functional groups on the surface of MXene. Prior art literature
[0007] Korean Registered Patent Publication No. 10-1480009, registered on Dec. 31, 2014. Korean Registered Patent Publication No. 10-1408925, registered on June 11, 2014. The problem to be solved
[0008] The present invention was developed to resolve the above-mentioned problems, and the technical problem is to provide a MXene-polymer composite that can prevent poor processability and surface protrusions caused by the high mixing amount of commonly used carbon black, a semiconducting layer for power cables including the same, and a power cable. means of solving the problem
[0009] In order to solve the above technical problem, the present invention provides a MXene-polymer composite characterized by comprising 1 to 40 weight% of MXene flakes; 40 to 89 weight% of a polyolefin-based matrix resin; and 0.01 to 20 weight% of a polyolefin-based polymer additive.
[0010] In the present invention, the polyolefin-based matrix resin is characterized by being composed of homo-polypropylene, random-polypropylene, a copolymer of polypropylene mixed with an elastomer, or a mixture thereof.
[0011] In the present invention, the MXene flake is Ti2C, (Ti 0.5 ,Nb 0.5It is characterized by being composed of )2C, V2C, Nb2C, Mo2C, Ti3C2, Ti3CN, Zr3C2, Hf3C2, Ti4N3, Nb4C3, Ta4C3, Mo2TiC2, Cr2TiC2, Mo2Ti2C3 or a mixture thereof.
[0012] In the present invention, the polyolefin-based polymer additive is characterized by including a functional group that reacts with one or more of the hydroxyl group (-OH), carbonyl group (C=O), and fluorine group (-F) on the surface of the MXene flake to induce chemical bonding.
[0013] In the present invention, the MXene-polymer composite is 10 -6 to 10 4 It is characterized by having a volume resistivity in the range of Ω·cm.
[0014] In the present invention, the MXene-polymer composite is characterized by having a root mean square (RMS) of 50 nm RMS or less.
[0015] In order to solve the other technical problems mentioned above, the present invention provides a semiconducting layer for a power cable characterized by including the MXene-polymer composite.
[0016] In order to solve the above-mentioned other technical problem, the present invention provides a power cable characterized by comprising: a conductor; and a semiconducting layer formed by coating a MXene-polymer composite of any one of claims 1 to 6 on the outside of the conductor. Effects of the invention
[0017] According to the present invention as a means for solving the above problem, during the melt mixing of MXene flakes, a polyolefin matrix resin, and a polyolefin polymer additive, the dispersion of MXene flakes is facilitated through the chemical reaction between the polyolefin miscible polymer of the polyolefin matrix resin and the polyolefin polymer additive and the MXene flakes, and there is an effect that volume resistivity can be reduced and surface smoothness can be improved even with only a small amount of MXene flakes. Therefore, by applying the MXene-polymer composite to the semiconducting layer of a power cable, it is possible to alleviate electric field concentration and suppress insulation breakdown. Specific details for implementing the invention
[0018] The present invention will be described in detail below.
[0019] The present invention relates to a MXene-polymer composite having a two-dimensional structure, comprising 1 to 40 weight% of MXene flakes, 40 to 89 weight% of a polyolefin-based matrix resin, and 0.01 to 20 weight% of a polyolefin-based polymer additive, wherein the MXene flakes are uniformly dispersed within the polyolefin-based matrix resin and volume resistivity is efficiently reduced, and the surface smoothness after molding is lowered due to the inherent two-dimensional structure.
[0020] MXene in flake form is a two-dimensional crystalline transition metal carbide that has electrical conductivity and can be represented by the following chemical formula 1.
[0021] [Chemical Formula 1]
[0022] M n+1 X n T x
[0023] In the above Chemical Formula 1, M is an early transition metal, X includes at least one of carbon and nitrogen, and n is an integer from 1 to 3. Tx represents functional groups bonded to the surface of MXene, and may be one or more of a hydroxyl group (-OH), a carbonyl group (C=O), and a fluorine group (-F).
[0024] According to Chemical Formula 1, examples of MXene flakes include Ti2C, (Ti 0.5 ,Nb 0.5 )2C, V2C, Nb2C, Mo2C, Ti3C2, Ti3CN, Zr3C2, Hf3C2, Ti4N3, Nb4C3, Ta4C3, Mo2TiC2, Cr2TiC2, Mo2Ti2C3 or a mixture thereof may be used.
[0025] If MXene flakes are included in an amount of less than 1% by weight based on the total weight of the MXene-polymer composite, there is a disadvantage in that the volume resistivity of the composite cannot be reduced, and furthermore, dispersion within the polyolefin matrix resin becomes difficult due to a lack of functional groups such as hydroxyl groups (-OH). On the other hand, if MXene flakes are included in an amount exceeding 40% by weight, there is a disadvantage in that the viscosity of the MXene-polymer composite increases, making it difficult to process the composite, and it is undesirable as it may be accompanied by unexpected chemical reactions with molecules. Accordingly, it is preferable that MXene flakes be included in a range of 1 to 40% by weight.
[0026] The polyolefin matrix resin is a matrix composed of polyolefin resin that provides a space for dispersed MXene flakes. This polyolefin matrix resin may be composed of homo-polypropylene, random-polypropylene, a copolymer of polypropylene mixed with an elastomer, or a mixture thereof.
[0027] The polyolefin matrix resin may be included in a range of 40 to 89 weight percent based on the total weight of the MXene-polymer composite. If the polyolefin matrix resin is less than 40 weight percent, it cannot act as a support within the MXene-polymer composite, resulting in poor physical properties. Consequently, it is used as a semiconducting layer surrounding a conductor, but it fails to provide sufficient electrical properties and has the disadvantage of easily peeling off from the surface of the conductor due to external impact. If the polyolefin matrix resin exceeds 89 weight percent, the amount of MXene flakes and polyolefin polymer additives becomes relatively small, making it difficult for the MXene flakes to be uniformly dispersed or to help reduce the volume resistivity of the MXene-polymer composite.
[0028] Polyolefin-based polymer additives induce interaction between the polyolefin matrix resin and the MXene flakes, and may be included in a range of 0.01 to 20 weight percent based on the total weight of the MXene-polymer composite. If the polyolefin-based polymer additive is less than 0.01 weight percent, it is an insufficient amount to contribute to uniformly dispersing the MXene flakes in the polyolefin matrix resin, and if it exceeds 20 weight percent, it does not produce a better effect on the dispersibility of the MXene flakes compared to when an amount less than that is added, so it is desirable not to use more than 20 weight percent for economic reasons.
[0029] It is preferable that the polyolefin-based polymer additive includes a functional group that reacts with one or more of the hydroxyl group (-OH), carbonyl group (C=O), and fluorine group (-F) on the surface of the MXene flake to induce chemical bonding.
[0030] A MXene-polymer composite comprising 1 to 40 weight% of the aforementioned MXene flakes, 40 to 89 weight% of a polyolefin-based matrix resin, and 0.01 to 20 weight% of a polyolefin-based polymer additive is 10 -6 to 10 4It can have a volume resistivity in the range of Ω·cm and has material properties with a root-mean-square (RMS) of 50 nm RMS or less.
[0031] As such, by introducing MXene flakes, a polyolefin matrix resin, and a polyolefin polymer additive that reacts with the MXene flakes and can be mixed with the polyolefin matrix resin, the volume resistivity can be reduced as the MXene flakes are uniformly dispersed in the polyolefin matrix resin, and there is an advantage of being able to reduce surface smoothness due to the unique two-dimensional structure. In particular, the MXene-polymer composite has excellent electrical conductivity and superior surface smoothness due to the MXene flakes, so it has the advantage of being usable as a semiconducting layer for power cables and as a power cable formed by coating such a semiconducting layer onto a conductor.
[0033] The embodiments of the present invention will be described in more detail below. However, the following embodiments are provided merely to aid in understanding the present invention and do not limit the scope of the present invention.
[0034] <Example 1>
[0035] 89 wt% homo-polypropylene resin, 10 wt% maleic anhydride-grafted polypropylene (maleic anhydride-polypropylene), and Ti3C2T x A composition was prepared by simultaneously introducing a mixture of 1 wt% of MXene flakes having the composition into a melt mixer preheated to 200°C and mixing for 15 minutes. The prepared composition was pressurized for 10 minutes in a hot press molding machine preheated to 200°C, then transferred to a press molding machine set to a temperature of 10°C and rapidly cooled, thereby producing a flat composite specimen.
[0036] <Example 2>
[0037] 85.5 wt% homo-polypropylene resin, 9.5 wt% maleic anhydride-grafted polypropylene (maleic anhydride-polypropylene), and Ti3C2T x A composition was prepared by simultaneously introducing a mixture of 5% by weight of MXene flakes having the composition into a melt mixer preheated to 200°C and mixing for 15 minutes. The prepared composition was pressurized for 10 minutes in a hot press molding machine preheated to 200°C, then transferred to a press molding machine set to a temperature of 10°C and rapidly cooled, thereby producing a flat composite specimen.
[0038] <Example 3>
[0039] 81 wt% homo-polypropylene resin, 9 wt% maleic anhydride-grafted polypropylene (maleic anhydride-polypropylene), and Ti3C2T x A mixture consisting of 10% by weight of MXene flakes having the composition was simultaneously introduced into a melt mixer preheated to 200°C and mixed for 15 minutes to prepare a composition. The prepared composition was pressurized for 10 minutes in a hot press molding machine preheated to 200°C, then transferred to a press molding machine set to a temperature of 10°C and rapidly cooled to produce a flat composite specimen.
[0040] <Comparative Example 1>
[0041] In Comparative Example 1, maleic anhydride-polypropylene was not added. That is, 90 wt% homo-polypropylene resin, Ti3C2T x A mixture consisting of 10% by weight of MXene flakes having the composition was simultaneously introduced into a melt mixer preheated to 200°C and mixed for 15 minutes to prepare a composition. The prepared composition was pressurized for 10 minutes in a hot press molding machine preheated to 200°C, then transferred to a press molding machine set to a temperature of 10°C and rapidly cooled to produce a flat composite specimen.
[0042] <Comparative Example 2>
[0043] In Comparative Example 2, general-purpose carbon black was added instead of maleic anhydride-polypropylene and MXene flakes. Specifically, a mixture consisting of 70% by weight of homo-polypropylene resin and 30% by weight of carbon black was simultaneously introduced into a melt mixer preheated to 200°C and mixed for 15 minutes to prepare a composition. The prepared composition was pressurized for 10 minutes in a hot press molding machine preheated to 200°C, then transferred to a press molding machine set to a temperature of 10°C and rapidly cooled to produce a flat composite specimen.
[0044] The above Examples 1 to 3 and Comparative Examples 1 and 2 are summarized as shown in Table 1 below.
[0045] division Examples Comparative example 1 2 3 1 2 Homo-polypropylene 89 85.5 81 90 70 Maleic anhydride-polypropylene 10 9.5 9 - - Maxine flakes 1 5 10 10 - Carbon Black - - - - 30 Unit: Weight %
[0046] Referring to Table 1, it can be seen that Example 1 consists of 90 wt% homo-polypropylene, 10 wt% maleic anhydride-polypropylene, and 1 wt% MXene flakes without adding carbon black, Example 2 consists of 85.5 wt% homo-polypropylene, 9.5 wt% maleic anhydride-polypropylene, and 5 wt% MXene flakes excluding carbon black, just like in Example 1, and Example 3 also consists of 81 wt% homo-polypropylene, 9 wt% maleic anhydride-polypropylene, and 10 wt% MXene flakes without adding carbon black, just like in Example 1. Unlike Examples 1 to 3, Comparative Example 1 consists of 90% by weight of homo-polypropylene and 10% by weight of MXene flakes without adding maleic anhydride-polypropylene and carbon black, and Comparative Example 2 consists of 70% by weight of homo-polypropylene and 30% by weight of carbon black without adding maleic anhydride-polypropylene and MXene flakes.
[0047] <Test Example 1>
[0048] In this test example, the volume resistivity, tensile strength, elongation, and surface roughness of the semiconducting compositions according to Examples 1 to 3 and Comparative Examples 1 and 2 were analyzed. In this regard, the volume resistivity (Ω·cm) was measured at a DC applied voltage of 10 V, and the tensile strength was measured at a speed of 30 mm / min using a Universe Materials Testing Machine after preparing a dumbbell-shaped specimen as specified in ASTM D 638. For the elongation, the elongation was measured at a speed of 30 mm / min using a Universe Materials Testing Machine after preparing a dumbbell-shaped specimen as specified in ASTM D 638, and the surface roughness was analyzed for the presence and distribution of protrusions on the surface of the specimen using an Atomic Force Microscope, and the height of the protrusions was calculated as the mean square roughness. The results are shown in Table 2 below.
[0049] division Volume resistance (Ω·cm) Tensile strength (MPa) Elongation (MPa) Root mean square (nm) Example 1 6.22E17 19.4 892.3 7.54 Example 2 7.24E10 22.9 743.0 10.45 Example 3 5.36 21.2 623.5 9.24 Comparative Example 1 826.E5 20.6 38.2 25.62 Comparative Example 2 7.15 15.8 1.8 76.23
[0050] Referring to Table 2, in the case of Examples 1 to 3 in which MXene flakes were mixed as fillers, the volume resistivity decreased according to the content, and the volume resistivity of the semiconducting composition containing 10% by weight or more of MXene flakes was found to be suitable as a conventional semiconducting composition. In addition, both their tensile strength and elongation satisfied the standard values for a semiconducting composition. Furthermore, it was confirmed that the surface roughness of the composites mixed with MXene flakes as fillers was improved.
[0051] Unlike in Examples 1 to 3, in Comparative Example 1, which did not contain maleic anhydride-polypropylene, it was confirmed that volume resistivity, tensile strength, and elongation were all poor. In Comparative Example 2, which contained commonly used carbon black, the volume resistivity was adequate, but mechanical properties including tensile strength and elongation were significantly degraded due to the excessive amount of carbon black, and surface roughness was also found to be very high.
[0053] In summary, the present invention relates to a polymer composite comprising MXene flakes, and is significant in that by introducing MXene flakes, a polyolefin matrix resin, and a polyolefin polymer additive that reacts with the MXene flakes and can be mixed with the polyolefin matrix resin, it is possible to uniformly disperse MXene flakes with excellent electrical conductivity within the polyolefin matrix resin and efficiently reduce volume resistivity, as well as reduce the smoothness of the surface after molding due to its unique two-dimensional structure.
[0054] The foregoing description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains will be able to make various modifications and variations within the scope of the essential characteristics of the present invention. Accordingly, the embodiments disclosed in the present invention are intended to explain, not to limit, the technical concept of the present invention, and the scope of the technical concept of the present invention is not limited by such embodiments. The scope of protection of the present invention shall be interpreted by the claims, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of the present invention.
Claims
Claim 1 A MXene-polymer composite for a semiconducting layer of a power cable, comprising: 1 to 40 weight% of MXene flakes; 40 to 89 weight% of a polyolefin-based matrix resin; and 0.01 to 20 weight% of a polyolefin-based polymer additive comprising a functional group that reacts with one or more of a hydroxyl group (-OH), a carbonyl group (C=O), and a fluorine group (-F) on the surface of the MXene flakes to induce chemical bonding; wherein the composite is characterized by having a room-mean-square (RMS) of 50 nm RMS or less. Claim 2 A MXene-polymer composite for a semiconducting layer of a power cable according to claim 1, characterized in that the polyolefin-based matrix resin comprises homo-polypropylene, random-polypropylene, a copolymer of polypropylene mixed with an elastomer, or a mixture thereof. Claim 3 In claim 1, the MXene flake is Ti2C, (Ti 0.5 ,Nb 0.5 MXene-polymer composite for a semiconducting layer of a power cable, characterized by being composed of )2C, V2C, Nb2C, Mo2C, Ti3C2, Ti3CN, Zr3C2, Hf3C2, Ti4N3, Nb4C3, Ta4C3, Mo2TiC2, Cr2TiC2, Mo2Ti2C3 or a mixture thereof. Claim 4 delete Claim 5 In claim 1, the MXene-polymer composite is 10 -6 to 10 4 MXene-polymer composite for a semiconducting layer of a power cable, characterized by having a volume resistivity in the range of Ω·cm. Claim 6 delete Claim 7 A semiconducting layer for a power cable characterized by comprising a MXene-polymer composite of any one of claims 1 to 3 and 5. Claim 8 A power cable characterized by comprising: a conductor; and a semiconducting layer formed by coating the outside of the conductor with a MXene-polymer composite of any one of claims 1 to 3 and 5.
Citation Information
Patent Citations
Polyolefin master batch and preparation method thereof
CN110982141A
High voltage cable thermoplastic semiconducting shielding material and preparation method thereof
CN110498964A
New composition and use thereof
KR1020180029109A